please solve. answer is (x-2) (x+2+y)
Attachments:
![](https://hi-static.z-dn.net/files/da0/1e4a950a8bd58048fe85128406434321.jpg)
Answers
Answered by
5
Here is the answer..
![x {}^{2} - 2y + xy - 4 \\ = x {}^{2} + xy - 2y - 4 \\ = x(x +y ) - 2(y + 2 ) x {}^{2} - 2y + xy - 4 \\ = x {}^{2} + xy - 2y - 4 \\ = x(x +y ) - 2(y + 2 )](https://tex.z-dn.net/?f=x+%7B%7D%5E%7B2%7D++-+2y+%2B+xy+-++4+%5C%5C+%3D+x+%7B%7D%5E%7B2%7D++%2B+xy+-+2y+-+4+%5C%5C++%3D+x%28x+%2By+%29++-+2%28y++%2B+2+%29)
![\therefore (x - 2)(x + y + 2) \therefore (x - 2)(x + y + 2)](https://tex.z-dn.net/?f=+%5Ctherefore+%28x+-+2%29%28x+%2B+y+%2B+2%29)
Hence ,
Final Answer =>
![\texttt{(x - 2)(x + y + 2)} \texttt{(x - 2)(x + y + 2)}](https://tex.z-dn.net/?f=+%5Ctexttt%7B%28x+-+2%29%28x+%2B+y+%2B+2%29%7D+)
Hence ,
Final Answer =>
Answered by
1
QUESTION......
SOLVE IT :-![{x}^{2} -2y + xy - 4 {x}^{2} -2y + xy - 4](https://tex.z-dn.net/?f=%7Bx%7D%5E%7B2%7D+-2y+%2B+xy+-+4)
SOLUTION........
This could be solved with the process of factorisation ;
![{x}^{2} -2y + xy - 4 {x}^{2} -2y + xy - 4](https://tex.z-dn.net/?f=%7Bx%7D%5E%7B2%7D+-2y+%2B+xy+-+4)
=![{x}^{2} + xy- 2y - 4 {x}^{2} + xy- 2y - 4](https://tex.z-dn.net/?f=%7Bx%7D%5E%7B2%7D+%2B+xy-+2y+-+4)
HERE WE HAVE MAKE PAIR OF TERMS :-
1ST PAIR ARE :-
![{x}^{2} + xy {x}^{2} + xy](https://tex.z-dn.net/?f=%7Bx%7D%5E%7B2%7D+%2B+xy)
2ND PAIR IS :-
![2y - 4 2y - 4](https://tex.z-dn.net/?f=2y+-+4)
NOW NEXT STEP IS TO FIND COMMON IN BOTH THE PAIRS .
In ,
i)
"x" is common .
ii)
"2" is common.
So,
![{x}^{2} + xy- 2y - 4 {x}^{2} + xy- 2y - 4](https://tex.z-dn.net/?f=%7Bx%7D%5E%7B2%7D+%2B+xy-+2y+-+4)
=![x(x+y) - 2(y+2) <br /><br />= [tex] (x-2) (x+y+2) x(x+y) - 2(y+2) <br /><br />= [tex] (x-2) (x+y+2)](https://tex.z-dn.net/?f=+x%28x%2By%29+-+2%28y%2B2%29+%3Cbr+%2F%3E%3Cbr+%2F%3E%3D+%5Btex%5D+%28x-2%29+%28x%2By%2B2%29+)
AS "y" IS TAKEN COMMON IT IS TAKEN AS SINGLE.
ANSWER IS :-
![(x-2) (x+y+2). (x-2) (x+y+2).](https://tex.z-dn.net/?f=+%28x-2%29+%28x%2By%2B2%29.)
BE BRAINLY!!!
SOLVE IT :-
SOLUTION........
This could be solved with the process of factorisation ;
=
HERE WE HAVE MAKE PAIR OF TERMS :-
1ST PAIR ARE :-
2ND PAIR IS :-
NOW NEXT STEP IS TO FIND COMMON IN BOTH THE PAIRS .
In ,
i)
ii)
So,
=
AS "y" IS TAKEN COMMON IT IS TAKEN AS SINGLE.
ANSWER IS :-
BE BRAINLY!!!
Similar questions